Contribution of the imagery radar SAR-ERS to the analysis of the geometry of the recent deformation in the Beni Snassen mounts (North-eastern Morocco) - (:unkn) unknown (My University, 2009)
Image processing techniques already allow the operational use of radar satellite SAR-ERS imagery for cartography. Its use in North-eastern Morocco made it possible to extract the geometry of the deformation. Three directions of major faults oriented NW-SE, NE-SW and ENE-WSW appear to the breadth of the main morphological units. The arrangement and the recent character of the sets of these faults are confirmed on the field. This was used to establish a model of structural evolution of the Beni Snassen mounts within the framework of the evolution of the maghrebin chains in context of collision between the African - European lithospheric plates.
Keywords: African Research